Grout material, grout mortar composition and cured body
A dicalcium silicate compound-based grout material with specific properties improves fluidity and self-healing, addressing cracking and explosion risks, ensuring structural integrity and safety under temperature changes.
Patent Information
- Application Number
- JP2023098539
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-26
AI Technical Summary
Conventional grout materials suffer from low fluidity, leading to cracks in cured products, poor self-healing effects, and potential explosion due to temperature changes, posing risks to structural integrity and safety.
A grout material containing a dicalcium silicate compound with specific average particle diameter, aspect ratio, and roundness, combined with cement, expansive agents, gas foaming materials, and water reducers, enhances fluidity, suppresses bleeding, and improves fire resistance and carbonation resistance.
The grout material achieves high fluidity, reduces bleeding, and enhances self-healing and fire resistance, maintaining structural integrity under thermal stress.
Smart Images

Figure 2024179578000001 
Figure 2024179578000002 
Figure 2024179578000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a grout material, a grout mortar composition, and a hardened body obtained by using the grout mortar composition, which are used in the civil engineering and construction industries. [Background technology]
[0002] Grout materials are used to improve the workability and filling properties of mortar and concrete and to facilitate smooth grouting work. Its main applications include the construction of underground structures, the installation of bridge supports, the installation of various types of machinery, and the filling of gaps in walls and columns in earthquake reinforcement. In order to fill and integrate gaps in structures, it is required that it have (1) the required fluidity depending on the filling location and filling method, (2) non-shrinkage properties that prevent bleeding, settlement, and the generation of voids after filling, and (3) various strengths required depending on the conditions of use of the structure (for example, see non-patent document 1).
[0003] Since the volume of hardened cement decreases as the cement hydrates or dries, there is a risk that cracks will occur and that the adhesion performance to existing structures will decrease. The occurrence of cracks not only mars the aesthetic appearance, but also has the risk of adversely affecting the stability, waterproofing, and watertightness of the structure. Therefore, expansive materials used to compensate for cement shrinkage, prevent cracking, and maintain adhesion to structures include, for example, 3CaO·3Al2O3·CaSO4 (auin), calcium sulfoaluminate-based materials (auin-based expansive materials) whose main components are CaSO4 and CaO, lime-based materials (lime-based expansive materials) whose main component is free lime, and expansive materials containing free lime, hydraulic substances, and gypsum.
[0004] A grout material has been proposed that combines cement, expansive materials, and specific water-reducing agents to have low temperature dependency, extremely high fluidity and filling retention effects, and long-term strength-enhancing effects (see, for example, Patent Document 1). Furthermore, a high-strength grout material has been proposed that has excellent fluidity, suppresses bubble generation, and maintains an optimal length change rate and volume expansion rate (see, for example, Patent Document 2).
[0005] However, conventional grout materials have a problem that they have low fluidity, cracks occur in the hardened body, and even after cracks occur, they have a low self-healing effect. In addition, in structures using conventional grout materials, if the temperature rises rapidly due to a fire or other cause, the grouted area may explode, which may cause problems in guiding people left inside to the outside safely. For this reason, emulsions such as those described in Patent Document 3 are mixed in to create a grout with a strength of 80 N / mm 2 Known examples of fire-resistant cement compositions having the above compressive strength include a method for producing explosion-resistant cement mortar, as described in Patent Document 4, in which cement is mixed with water, cellulose fiber is added and uniformly dispersed, and then fine aggregate is mixed. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 3894780 [Patent Document 2] International Publication No. 2007 / 029399 Brochure [Patent Document 3] JP 2014-076917 A [Patent Document 4] Patent No. 4878086 [Non-patent literature]
[0007] [Non-Patent Document 1] New Admixtures for Cement and Concrete, pp. 304-307, Yoshio Kasai and Etsuro Sakai, Gijutsu Shoin, published January 15, 2007 Summary of the Invention [Problem to be solved by the invention]
[0008] As mentioned above, Patent Document 3 describes a method for blending an emulsion with a strength of 80 N / mm 2 Although fire-resistant cement compositions having the above compressive strength have been proposed, they are difficult to work with to make grout mortar, and are difficult to use as grout materials. In addition, the manufacturing method described in Patent Document 4 involves mixing cement with water, adding cellulose fiber and dispersing it uniformly, and then mixing fine aggregate, which is a time-consuming method for work at the construction site, and therefore poses a problem in using it as a grout material. Therefore, an object of the present invention is to provide a grout material, a grout mortar composition, and a hardened body that have high fluidity, suppress bleeding, and further enhance the self-healing effect, as well as improved fire resistance and resistance to neutralization after exposure to heat. [Means for solving the problem]
[0009] The present invention has been made to solve the above problems, and the inventors have made various efforts to solve the above problems, and as a result, have found that by containing a grout admixture containing a dicalcium silicate compound with a specific average particle size and average aspect ratio measured by microscopic observation, it is possible to achieve high fluidity, suppress bleeding, and further enhance the self-healing effect, and also improve fire resistance and resistance to carbonation after exposure to heat, and have completed the present invention. The gist of the present invention is as follows. [1] A grout material comprising a grout admixture containing a di-calcium silicate compound having an average particle size of 5 to 100 μm as measured by microscopic observation and an average aspect ratio expressed as (major axis diameter / minor axis diameter) of 1.3 or more, cement, an expansive agent and / or a hardening accelerator, a gas foaming agent, a water reducing agent, and fine aggregate. [2] The grout material according to [1] above, wherein the average circularity of the di-calcium silicate compound, expressed as (4 × pi × area / (perimeter squared)), is 0.8 or less. [3] The chemical composition of the grout admixture is 44 to 75 parts by mass of CaO, 18 to 55 parts by mass of SiO2, 1 to 3 parts by mass of Al2O3, 0 to 5 parts by mass of MgO, and 0 to 2 parts by mass of SO3 per 100 parts by mass of the total of CaO, SiO2, Al2O3, MgO, and SO3, and the Blaine specific surface area value of the di-calcium silicate compound is 2,000 to 6,000 cm 2 / g. The grout material according to [1] or [2] above. [4] The grout material according to any one of [1] to [3] above, wherein the content of the fine aggregate is 40 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the cement. [5] A grout mortar composition comprising the grout material according to any one of [1] to [4] above and water. [6] A hardened body obtained by using the grout mortar composition described in [5] above. Effect of the Invention
[0010] According to the present invention, it is possible to provide a grout material, a grout mortar composition, and a hardened body which have high fluidity, suppress bleeding, and further enhance the self-healing effect, as well as improved fire resistance and resistance to neutralization after exposure to heat. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. In this specification, parts and percentages are by weight unless otherwise specified. In addition, the grout mortar referred to in this specification is a general term for paste without coarse aggregate and mortar containing fine aggregate.
[0012] The grout material of the present invention is a grout material containing a grout admixture containing a di-calcium silicate compound having an average particle size of 5 to 100 μm as measured by microscopic observation and an average aspect ratio expressed as (major axis diameter / minor axis diameter) of 1.3 or more, cement, an expansive agent and / or a hardening accelerator, a gas foaming substance, a water reducing agent, and fine aggregate.
[0013] [Grout admixture] The grout admixture according to this embodiment contains a di-calcium silicate compound.
[0014] <Dicalcium silicate compound> The di-calcium silicate compound according to the present invention is characterized in that it has an average particle size of 5 to 100 μm and an average aspect ratio represented by (major axis diameter / minor axis diameter) of 1.3 or more. In addition, the di-calcium silicate compound preferably has an average circularity (hereinafter sometimes referred to as "average circularity") expressed as (4 x pi x area / (perimeter squared)) of 0.8 or less. The average particle size of the di-calcium silicate (hereinafter sometimes referred to as "DCS") compound must be in the range of 5 to 100 μm, as described above. If the average particle size is out of the range of 5 to 100 μm, there is a tendency that the fluidity is impaired, the self-healing effect is reduced, and the compressive strength residual ratio with respect to the heating temperature is significantly reduced. From the above viewpoints, the average particle size of the DCS compound is more preferably in the range of 10 to 90 μm, and even more preferably in the range of 15 to 80 μm.
[0015] The average aspect ratio of the di-calcium silicate compound, expressed by (major axis diameter / minor axis diameter), is essential to be 1.3 or more, as described above. If the average aspect ratio is smaller than 1.3, the neutralization depth after heating tends to be large. From the above viewpoints, the average aspect ratio is more preferably 1.5 or more, and even more preferably 1.7 or more.
[0016] In addition, the average circularity of the di-calcium silicate compound is preferably 0.8 or less, as described above. If the average circularity is 0.8 or less, it is advantageous in terms of improving fluidity and fire resistance. From the above viewpoint, the average circularity is more preferably 0.75 or less, and even more preferably 0.7 or less. There is no particular limit to the lower limit of the average circularity, but it is usually about 0.5. As described above, the average circularity indicates the average value of the circularity expressed as 4×pi×area / (square of circumference).
[0017] (Methods for measuring average particle size, average aspect ratio, and average roundness) The average particle size, average aspect ratio, and average circularity of the di-calcium silicate compound can be measured as follows. The average particle size, average aspect ratio, and average circularity can be adjusted to fall within the above ranges, for example, by adjusting the grinding time.
[0018] (1) For a plurality of di-calcium silicate compounds, images of the di-calcium silicate compounds projected onto a plane are obtained. Such an image can be obtained, for example, by photographing a plurality of di-calcium silicate compounds from one direction, or by photographing a cross section of a porous layer containing the di-calcium silicate compounds.
[0019] (2) From the obtained image, the particle size, aspect ratio, and circularity (area, circumference) of each particle of the di-calcium silicate compound are measured. The particle size, aspect ratio, and circularity (area, circumference) can be measured using appropriate image analysis software (such as IMAGEJ). It is preferable that the number of particle points to be measured is in the range of 3,000 to 5,000. If there are 3,000 or more points, the measurement error will be small, and if there are 5,000 or less points, the physical burden on the person measuring will be small, so this is preferable.
[0020] (3) The average values of the measured particle size, aspect ratio, and circularity are calculated to obtain the average particle size, average aspect ratio, and average circularity. The aspect ratio is a value expressed as (major axis diameter) / (minor axis diameter). The closer this value is to 1, the closer it is to a perfect circle.
[0021] The di-calcium silicate compound in the present invention may contain MgO, R2O (R is an alkali metal), etc., so long as the total amount of the compound is 10 mass % or less. Also, the DCS compound in the present invention may contain a glass phase formed by quenching, so long as the total amount of the compound is 10 mass % or less.
[0022] (DCS compound fineness) The fineness of the di-calcium silicate compound is 2,000 to 6,000 cm in terms of Blaine specific surface area value (hereinafter sometimes referred to as "Blaine value"). 2 / g, and 2,500 to 5,000 cm 2 / g is more preferable. 2,000 ccm 2 / g or more, sufficient compressive strength and fire resistance are obtained. 2 If the content is less than 1 / g, resistance to carbonation after exposure to heat can be obtained.
[0023] (Production method of DCS compound) DCS compounds are obtained by mixing raw materials containing CaO, SiO2, and Al2O3, and subjecting them to heat treatment such as firing in a kiln or melting in an electric furnace. The heat treatment temperature depends on the composition of the raw materials, but is preferably 1,400°C or higher and 1,800°C or lower, more preferably 1,450°C or higher and 1,600°C or lower, and even more preferably 1,450°C or higher and 1,550°C or lower. If the temperature is 1,400°C or higher, the reaction proceeds efficiently, no unreacted Al2O3 remains, and dicalcium silicate is efficiently obtained. On the other hand, if the heat treatment temperature is 1,800°C or lower, coating is difficult to form during the heat treatment, operation is not difficult, and energy efficiency is good.
[0024] (DCS compound content) The content of the di-calcium silicate compound in the grout admixture is preferably 35% or more, more preferably 45% or more, and there is no particular upper limit to the content of the di-calcium silicate compound.
[0025] As a method for quantifying the dicalcium silicate compound in this admixture for grout, there is a Rietveld method by powder X-ray diffraction and the like.
[0026] <Chemical composition of admixture for grout> The admixture for grout according to this embodiment preferably has a chemical composition in which, with respect to a total of 100 parts of CaO, SiO2, Al2O3, MgO, and SO3, CaO is in the range of 44 to 75 parts, SiO2 is in the range of 18 to 55 parts, Al2O3 is in the range of 1 to 3 parts, MgO is in the range of 0 to 5 parts, and SO3 is in the range of 0 to 2 parts. More preferably, CaO is in the range of 49 to 70 parts, SiO2 is in the range of 23 to 50 parts, Al2O3 is in the range of 1 to 2 parts, MgO is in the range of 0 to 3 parts, and SO3 is in the range of 0 to 1 part. When within this range, there are advantages such as no extension in the time to reach a demoldable strength, maintenance of compressive strength, no extension in the time required for imparting fire resistance, and the ability to reduce the carbonation depth after heating, which is preferable.
[0027] Also, the admixture for grout according to this embodiment may further contain calcium carbonate in a range of 5 parts or less with respect to 100 parts of the admixture for grout. Containing calcium carbonate has advantages such as increasing the storage stability of the admixture for grout and improving the strength development of the manufactured concrete. From the above viewpoints, the content of calcium carbonate is more preferably in the range of 0.5 to 3 parts.
[0028] <Raw materials> The raw materials used for manufacturing the admixture for grout used in the present invention will be described.
[0029] <<Raw materials containing CaO>> The raw material containing CaO is not particularly limited. Examples include commercially available industrial raw materials such as quicklime (CaO), slaked lime (Ca(OH)2), and limestone (CaCO3). In addition, industrial wastes such as by - product slaked lime generated from acetylene production, fine powder generated from waste concrete blocks, etc. can also be applied within the range that does not inhibit the effects of the present invention. From the perspective of reducing non - energy - derived CO2 emissions during heat treatment, it is preferable in that one or more selected from industrial by - products containing CaO such as by - product slaked lime, fine powder generated from waste concrete blocks, municipal solid waste incineration ash, and sewage sludge incineration ash can be utilized. Among them, the use of by - product slaked lime with a lower amount of impurities compared to other industrial by - products is even more preferable.
[0030] Examples of by - product slaked lime include by - product slaked lime (there are wet and dry products depending on the method of producing acetylene gas) by - produced in the production process of acetylene gas by the calcium carbide method, and by - product slaked lime contained in the dust captured in the wet dust collection process of the calcium carbide electric furnace, such as acetylene by - product slaked lime. By - product slaked lime contains, for example, 65 - 95% (preferably 70 - 90%) calcium hydroxide, and in addition, 1 - 10% calcium carbonate and 0.1 - 6.0% (preferably 0.1 - 3.0%) iron oxide. These ratios can be confirmed by the mass loss determined by fluorescent X - ray measurement and differential thermal gravimetric analysis (TG - DTA) (Ca(OH)2: around 405°C - 515°C, CaCO3: around 650°C - 765°C). The volume - average particle diameter measured by the laser diffraction / scattering method is about 50 - 100 μm. Furthermore, in JIS K 0068 "Method for Measuring Moisture in Chemical Products", the moisture content measured by the drying loss method is preferably 10% or less. It may also contain sulfur compounds such as CaS, A12S3, and CaC2·CaS, but preferably 2% or less.
[0031] <<Raw material containing SiO2>> The raw materials containing SiO2 are not particularly limited. Examples include quartzite, silica sand, quartz, diatomaceous earth, etc., which are commercially available as industrial raw materials. Furthermore, various silica dusts generated as industrial by-products, such as silica fume and fly ash, can also be applied as long as they do not inhibit the effects of the present invention.
[0032] <<Raw materials containing Al2O3>> The raw materials containing Al2O3 are not particularly limited. Examples include Al2O3, aluminum hydroxide, bauxite, etc., which are commercially available as industrial raw materials. Note that bauxite is desirable because it contains Fe2O3, as well as SiO2 and TiO2, in addition to Al2O3. On the other hand, if the required amount of Al2O3 is contained in the raw materials containing CaO or SiO2, the raw materials containing Al2O3 may not be used.
[0033] <<MgO raw materials>> The MgO raw materials used in the present invention are not particularly limited. For example, magnesias such as fused magnesia, sintered magnesia, natural magnesia, and lightly burned magnesia can be used. The MgO raw materials referred to here are magnesium hydroxide (Mg(OH)2), magnesium carbonate (MgCO3), magnesite which is natural MgO, or sintered magnesia clinker obtained by firing natural magnesium carbonate in a rotary kiln, etc., and the fused magnesia clinker obtained by melting the sintered magnesia clinker in an electric furnace, etc., which are pulverized to a predetermined size and sieved.
[0034] <<Raw materials containing SO3>> The raw materials containing SO3 are not particularly limited. Examples include raw gypsum, anhydrite (anhydrous gypsum), burned gypsum (hemihydrate gypsum), desulfurized gypsum (dihydrate gypsum), etc.
[0035] <<Impurities>> The CaO raw material, SiO2 raw material, Al2O3 raw material, MgO raw material, and SO3 raw material may contain impurities, but this is not a problem as long as the effects of the present invention are not hindered. Specific examples of impurities include Fe2O3, TiO2, MnO, Na2O, K2O, P2O5, F, B2O3, and chlorine. Coexisting compounds include free calcium oxide, calcium hydroxide, calcium aluminate, calcium aluminosilicate, calcium ferrite, calcium aluminoferrite, calcium phosphate, calcium borate, magnesium silicate, leucite (K2O, Na2O)·Al2O3·SiO2, spinel MgO·Al2O3, magnetite Fe3O4, and sulfur compounds such as CaS, A12S3, and CaC2·CaS.
[0036] Of these impurities, the content of S (sulfur) in the di-calcium silicate compound is preferably 1.0% or less, more preferably 0.7% or less, and even more preferably 0.5% or less, calculated as oxide (SO3). By having the content of S or less than 1.0%, a sufficient carbonation (salt) promotion effect can be obtained, and the setting and hardening properties can be kept within an appropriate range. The content of S calculated as oxide (SO3) can be measured by fluorescent X-ray measurement. Note that S (sulfur) in the DCS compound may be present at about 2% calculated as oxide.
[0037] <Slag and / or pozzolanic material> The grout admixture of the present invention may contain slag and / or pozzolanic substances. The slag and / or pozzolanic substances are latent hydraulic substances, and are not particularly limited, but examples thereof include blast furnace slag (cooled blast furnace slag, granulated blast furnace slag), steelmaking slag (converter slag, electric furnace slag), fly ash, silica fume, metakaolin, pulp sludge incineration ash, sewage sludge incineration ash, volcanic glass fine powder, waste glass powder, etc. These may be used alone or in combination of two or more. Among these, ground granulated blast furnace slag, fly ash, silica fume, and metakaolin are preferred from the viewpoints of maintaining a sufficient compressive strength residual ratio and Young's modulus residual ratio after heating, as well as the effect of carbonation resistance after heating.
[0038] Furthermore, the blending ratio of the DCS compound to the slag and / or pozzolanic substance is not particularly limited, but a mass ratio of 10 / 1 to 1 / 10 is preferable, and a mass ratio of 5 / 1 to 1 / 5 is more preferable. By mixing DCS compounds with slag and / or pozzolanic substances (latent hydraulic substances) in the above-mentioned ranges, sufficient rust prevention effects, resistance to chloride ion penetration, inhibition of calcium ion leaching, and improved self-healing abilities can be obtained compared to when DCS compounds are used alone.
[0039] In addition, in the present invention, in order to maintain sufficient compressive strength residual ratio and Young's modulus residual ratio after heating, as well as the effect of carbonation resistance after heating, a cement admixture having a CaO / SiO2 molar ratio of 0.15 to 0.7 and an SO3 content of 0 to 3% can be used in combination with slag and / or pozzolanic substances. In this embodiment, industrial by-products containing non-hydraulic compounds such as γ-DCS can also be used. In this case, impurities coexist. Examples of such industrial by-products include steel slag.
[0040] <Manufacturing method of grout admixture> The grout admixture can be produced by mixing the above-mentioned raw materials and subjecting them to a high temperature of 1,000° C. or higher. The heat treatment method is not particularly limited, but can be performed, for example, using a rotary kiln or an electric furnace. The heat treatment temperature is not uniquely determined, but is usually performed in the range of about 1,000 to 1,800° C., and is often performed in the range of about 1,200 to 1,600° C.
[0041] <Blaine specific surface area of grout admixture> The Blaine specific surface area of this grout admixture is not particularly limited, but is preferably 1,500 cm 2 / g or more is preferable, and the upper limit is 8,000 cm 2 / g or less. In particular, 2,000 to 6,000 cm 2 / g is more preferable, and 4,000 to 6,000 cm 2 / g is most preferable. The Blaine specific surface area is 1,500 cm 2 / g or more, good material separation resistance is obtained and the carbonation (salt) promotion effect is sufficient. 2 / g or less, the power required for pulverization is not large, which is economical, and weathering is suppressed, thereby preventing deterioration of quality over time.
[0042] <Amount of grout admixture used> The amount of the grout admixture used is not particularly limited, but is preferably 1 to 30 parts, more preferably 2 to 25 parts, when the total amount of the cement and the grout admixture is 100 parts. If the amount of the grout admixture used is small, sufficient compressive strength residual ratio and Young's modulus residual ratio after heating, and carbonation resistance after heating may not be obtained, and if used excessively, a decrease in strength development may occur.
[0043] [cement] The cement used in the present invention is not particularly limited, and examples thereof include various cements such as normal, early strength, super early strength, low heat and medium heat, various mixed cements obtained by mixing these cements with blast furnace slag, fly ash and silica fume, environmentally friendly cements (eco-cements) manufactured using municipal waste incineration ash and sewage sludge incineration ash as raw materials, commercially available fine particle cements, etc. It is also possible to use various cements and various mixed cements in a fine powder form. Also, cements adjusted by increasing or decreasing the amount of components (e.g., gypsum) normally used in cements can be used. In the present invention, it is preferable to select ordinary Portland cement or high-early-strength Portland cement from the viewpoints of high fluidity, improved self-healing effect, and improved fire resistance.
[0044] The cement used in the present invention has a Blaine specific surface area of 2,500 cm from the viewpoint of production cost and strength development. 2 / g or more 7,000cm 2 / g or less, and 2 / g or more 6,000cm 2 / g or less is more preferable, and 2 / g or more 4,500cm 2 It is more preferable that the molecular weight is not more than 1 / g. The Blaine specific surface area value is determined in accordance with JIS R 5201 (physical testing method for cement).
[0045] [Expansion material] The expanding material used in the present invention is not particularly limited, and any material can be used as long as it generates an expansive hydrate and inhibits bleeding. Known expansive materials include free lime, free magnesia, calcium ferrite, ettringite, lime, and ettringite-lime composites, and are not particularly limited, but from the viewpoint of long-term stability, those containing free lime are preferred. Examples of those containing free lime include free lime-anhydrous gypsum, free lime-hydraulic compound, and free lime-hydraulic compound-anhydrous gypsum. In the present invention, it is preferable to use a free lime-hydraulic compound-anhydrous gypsum system because of its good expansion performance, and it is particularly preferable to use one having a free lime content of more than 40 mass %. Here, examples of the hydraulic compound include one or more of auin, calcium ferrite, calcium aluminoferrite, calcium silicate, calcium aluminate, etc. In the present invention, commercially available expanding materials can be used as the expanding material. Expansion agents are commercially available from various companies, and representative examples include Denka CSA #20 and Denka Power CSA manufactured by Denka Company Ltd., and Expan, Hyper Expan, N-EX, and Blaster manufactured by Pacific Materials Corporation, as well as crushed products of these agents.
[0046] The particle size of the expanding agent used in the present invention is not particularly limited, but it is preferable that the particle size is 2,000 cm2 or less in terms of Blaine specific surface area. 2 / g or more 25,000cm 2 / g or less is preferable, and 2,200 cm 2 / g or more 15,000cm 2 / g or less is preferable, and 2,400 cm 2 / g or more 10,000cm 2 / g or less is more preferable. By setting the Blaine specific surface area of the expanding material to the above lower limit or more, bleeding can be suppressed. Also, by setting the Blaine specific surface area of the expanding material to the above upper limit or less, sufficient expandability can be obtained.
[0047] The content of the expansive material used in the present invention is preferably 0.5 parts by mass or more and 20 parts by mass or less, more preferably 1.0 parts by mass or more and 18 parts by mass or less, and even more preferably 2 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of cement. When the content of the expansive material is equal to or more than the lower limit, it is easy to obtain a crack suppression effect. On the other hand, when the content of the expansive material is equal to or less than the upper limit, strength expression is good. When the content of the expansive material is within the above range, it is easy to obtain a grout material that satisfies the effects of the present invention, that is, a grout material that has a bleeding suppression effect, enhances fluidity, and improves self-healing effect and fire resistance.
[0048] [Gas foaming material] The gas foaming substance used in the present invention is used for the purpose of preventing the unhardened grout material from sinking or shrinking due to bleeding after application of the grout mortar composition. The gas foaming substance used in the present invention is not particularly limited as long as it generates gas after being mixed with water.
[0049] Examples of the gas foaming substance include oily substances such as vegetable oils and mineral oils. Examples of the gas foaming substance include powder substances such as flaky aluminum powder surface-treated with stearic acid and aluminum powder produced by an atomizing method. Examples of the gas foaming substance include nitrogen gas foaming substances that foam nitrogen gas under an alkaline atmosphere, such as azo compounds, nitroso compounds, and hydrazine derivatives. Examples of the gas foaming substance include percarbonates such as sodium percarbonate, potassium percarbonate, and ammonium percarbonate, perborates such as sodium perborate and potassium perborate, permanganates such as sodium permanganate and potassium permanganate, and peroxides such as hydrogen peroxide. As the gas foaming substance used in the present invention, it is preferable to use aluminum powder that has been surface-treated with stearic acid or the like, since this has a large effect of suppressing subsidence.
[0050] The nitrogen gas foaming substance used as the gas foaming substance in the present invention contains a compound that generates nitrogen gas by reacting with an alkali generated when the cement contained in the grout material is mixed with water, and may by-produce gases such as carbon monoxide, carbon dioxide, and ammonia. The nitrogen gas foaming substance used in the present invention is not particularly limited as long as it can be used to integrate the substance with a structure, to prevent the unhardened grout mortar from sinking or shrinking, and to improve the crack resistance when kept in a dry state.
[0051] The content of the gas foaming substance is preferably 0.0001 to 1 part by mass, more preferably 0.0005 to 0.5 parts by mass, and even more preferably 0.001 to 0.2 parts by mass, relative to 100 parts by mass of cement. By having the content of the gas foaming substance be equal to or higher than the lower limit, sufficient initial expansion effect and bleeding suppression effect can be imparted. Furthermore, by having the content of the gas foaming substance be equal to or lower than the upper limit, strength development is improved.
[0052] [Water reducing agent] The water reducing agent used in the present invention plays a role in aiding the dispersion of each material and imparting fluidity to the mixed grout mortar.
[0053] The water-reducing agent used in the present invention is not particularly limited, and examples thereof include naphthalene-based water-reducing agents, melamine-based water-reducing agents, aminosulfonic acid-based water-reducing agents, and polycarboxylic acid-based water-reducing agents. One or more of these water-reducing agents can be used in the present invention. Specific examples of water reducing agents include naphthalene-based water reducing agents such as "Leobuild SP-9 Series" manufactured by NMB Corporation, "Mighty 2000 Series" manufactured by Kao Corporation, and "Sunflow HS-100" manufactured by Nippon Paper Industries Co., Ltd. Melamine-based water reducing agents such as "Sikament 1000 Series" manufactured by Sika Japan Co., Ltd. and "Sunflow HS-40" manufactured by Nippon Paper Industries Co., Ltd. Aminosulfonic acid-based water reducing agents such as "Paric FP-200 Series" manufactured by Fujisawa Pharmaceutical Co., Ltd. Polycarboxylic acid-based water reducing agents such as "Leobuild SP-8 Series" manufactured by NMB Corporation, "Darlex Super 100PHX" manufactured by Grace Chemicals Co., Ltd., and "Chupol HP-8 Series" and "Chupol HP-11 Series" manufactured by Takemoto Oil & Fat Co., Ltd. Powdered water reducing agents are also available. Specifically, naphthalene-based water reducing agents include "Mighty 100" manufactured by Kao Corporation, "Sanyo Revlon P" manufactured by Sanyo Chemical Industries, and "Cellflow 110P" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Melamine-based water reducing agents include "Melment F10M" manufactured by BASF Pozzolith, and polycarboxylic acid-based water reducing agents include "CAD9000P" manufactured by Kao Corporation.
[0054] The content of the water reducing agent is preferably 0.1 to 2 parts by mass, more preferably 0.2 to 1.8 parts by mass, and even more preferably 0.3 to 1.0 parts by mass, based on 100 parts by mass of cement, in terms of solid content. By having the content of the water reducing agent be equal to or greater than the lower limit, sufficient fluidity can be obtained. Furthermore, by having the content of the water reducing agent be equal to or less than the upper limit, material separation can be suppressed.
[0055] [Fine aggregate] The chemical components of the fine aggregate used in the present invention are preferably such that the proportion of CaO is 85 mass% or more and the proportion of SiO2 is 0.2 mass% or more and 15 mass% or less. By having the proportions of CaO and SiO2 within the above ranges as the chemical components of the fine aggregate, a grout material having high fluidity, carbonation resistance, adhesive strength with reinforcing bars, and rust prevention properties can be obtained. The proportion of CaO is preferably 87% by mass or more, more preferably 89% by mass or more, and even more preferably 91% by mass or more. The upper limit of the proportion of CaO is not particularly limited, but is preferably 99% by mass or less, and more preferably 98.5% by mass or less. The proportion of SiO2 is preferably 0.25 mass % or more and 13 mass % or less, more preferably 0.3 mass % or more and 11 mass % or less, and further preferably 0.4 mass % or more and 10 mass % or less. In order to make the chemical composition of the fine aggregate fall within the above range and the range described below, silica sand, calcite, scapolite, which is a metamorphic rock, quartz, which is an igneous rock, potassium feldspar, etc. are mixed and prepared. The chemical composition is adjusted by mixing each rock while checking with fluorescent X-ray diffraction so that it falls within the range of the present invention. The chemical composition of the fine aggregate used in the present invention is calculated in terms of oxides.
[0056] As the fine aggregate used in the present invention, the same fine aggregate as that used in ordinary cement mortar and concrete can be used. That is, river sand, crushed stone, crushed sand, lime sand, silica sand, colored sand, artificial lightweight aggregate, etc. can be used, and these can also be combined. In particular, for applications aimed at increasing fluidity and achieving a self-healing effect, it is preferable to use siliceous silica sand or lime sand, and the grain size of the fine aggregate is preferably JIS No. 6 to JIS No. 8.
[0057] The content of the fine aggregate is preferably 40 parts by mass or more and 300 parts by mass or less, more preferably 45 parts by mass or more and 275 parts by mass or less, and even more preferably 50 parts by mass or more and 250 parts by mass or less, relative to 100 parts by mass of cement. By having the content of the fine aggregate within the above range, sufficient fluidity and self-healing effect can be obtained.
[0058] [Sudden hardwood] The hardening agent used in the present invention is not particularly limited as long as it promotes setting and increases strength in a short period of time. Examples of hardening agents that promote setting include calcium salts of organic acids such as calcium formate, nitrates, sulfates, carbonates, thiocyanates, amines, maleic anhydride, silicates such as water glass, aluminum sulfate, and aluminum salts such as alum, calcium aluminate (calcium aluminate), and aluminates. Among these, aluminates are preferred from the viewpoint of strength development, and it is preferable to include calcium aluminate (CA). Calcium aluminate is more preferred from the viewpoint of improving strength development when used in combination with gypsum. The amount of gypsum used is preferably 80 parts by mass or more and 250 parts by mass or less, more preferably 90 parts by mass or more and 220 parts by mass or less, and even more preferably 100 parts by mass or more and 200 parts by mass or less, relative to 100 parts by mass of calcium aluminate. When the content of gypsum is equal to or more than the lower limit, it becomes easier to obtain early hardening properties. In addition, when the content of gypsum is equal to or less than the upper limit, the strength development and self-healing effect are good. When the content of gypsum is within the above range, it is easy to obtain a grout material that improves the bleeding suppression effect, early hardening property, and self-healing effect of the grout mortar material that satisfies the effects of the present invention.
[0059] Calcium aluminate is a general term for a substance having hydration activity and composed mainly of CaO and Al2O3, which is obtained by mixing calcia raw materials and alumina raw materials, firing them in a kiln, or melting them in an electric furnace and cooling them, and can be used whether it is crystalline or amorphous. It is a material that hardens quickly and has high initial strength development. Alumina cement is a representative example of calcium aluminate, and commercially available products can usually be used. For example, Alumina Cement No. 1 and Alumina Cement No. 2 can be used. Among them, amorphous calcium aluminate that is melted and then rapidly cooled is preferred because it hardens in a shorter time than alumina cement and has high initial strength development thereafter. Among calcium aluminates, the molar ratio of CaO to Al2O3 (CaO / Al2O3 molar ratio) is preferably 1.2 to 3.0, more preferably 1.7 to 2.5. By having the molar ratio within the above range, the curing time can be further shortened and the early strength development can be improved.
[0060] In the present invention, the impurities contained in calcium aluminate are preferably 15% by mass or less from the viewpoint of early strength development, and more preferably 10% by mass or less. Here, the impurities refer to substances other than CaO and Al2O3. When the impurities are 15% by mass or less, the hardening time can be shortened, and furthermore, the material can be sufficiently hardened even at low temperatures. Representative examples of impurities include silicon oxide, magnesium oxide, and sulfur oxide, and in addition, organic substances, alkali metal oxides, alkaline earth metal oxides, titanium oxide, iron oxide, alkali metal halides, alkaline earth metal halides, alkali metal sulfates, and the alkaline earth metal sulfates are partially substituted or solid-dissolved in CaO or Al2O3. However, the impurities are not limited to these.
[0061] The vitrification rate of calcium aluminate used in the present invention is preferably 70% by mass or more, more preferably 90% by mass or more, in terms of reaction activity. When the vitrification rate is 70% by mass or more, the initial strength development is not reduced. The vitrification rate of calcium aluminate is preferably 70% by mass or more, more preferably 90% by mass or more, in terms of reaction activity. The vitrification rate is determined by measuring the main peak area S of the crystalline mineral of a measurement sample in advance by powder X-ray diffraction method, heating the sample at 1,000°C for 2 hours, and then slowly cooling the sample at a cooling rate of (1 to 10°C) / min, determining the main peak area S0 of the crystalline mineral after heating by powder X-ray diffraction method, and using these S0 and S values, calculating the vitrification rate using the following formula: X Calculate. Vitrification rate X (mass%)=100×(1-S / S0) The particle size of calcium aluminate is suitable for early strength development, with a Blaine specific surface area of 3,000 cm 2 / g or more is preferable, and 5,000 cm2 When the particle size of calcium aluminate is equal to or greater than the lower limit, the hardening time is shortened, resulting in good early strength development and good self-healing performance.
[0062] The content of the hardening agent used in the present invention is preferably 1 to 30 parts by mass, more preferably 3 to 25 parts by mass, and even more preferably 5 to 20 parts by mass, relative to 100 parts by mass of cement. In addition, when calcium aluminate is contained as the hardening agent, the content of calcium aluminate is preferably 2 to 20 parts by mass, more preferably 3 to 18 parts by mass, and even more preferably 4 to 15 parts by mass, relative to 100 parts by mass of cement. When the content of the hardening agent is equal to or more than the lower limit, it is easy to obtain early hardening properties and crack suppression effects. In addition, when the content of the hardening agent is equal to or less than the upper limit, strength expression is good. When the content of the hardening agent is within the above range, it is easy to improve the self-healing effect, and a grout mortar material that satisfies the effects of the present invention can be obtained.
[0063] [others] In the present invention, one or more of the following may be used within a range that does not adversely affect performance: setting regulators, air-entraining agents, rust inhibitors, water repellents, antibacterial agents, colorants, antifreeze agents, nitrites, siliceous powders, fine limestone powder, finely cooled blast furnace slag powder, sewage sludge incineration ash and its molten slag, urban waste incineration ash and its molten slag, and pulp sludge incineration ash; defoamers, thickeners, shrinkage reducing agents, fibrous materials such as steel fiber, vinylon fiber, carbon fiber, and wollastonite fiber; polymers; clay minerals such as bentonite and sepiolite; and anion exchangers such as hydrotalcite.
[0064] In the grout material of the present invention, the method of mixing the respective materials is not particularly limited, and the respective materials may be mixed at the time of application, or a part or all of the materials may be mixed in advance. As the mixing device, any existing device such as a tilting mixer, an omni mixer, a Henschel mixer, a V-type mixer, and a Nauta mixer can be used.
[0065] [Grout mortar composition] The grout mortar composition of the present invention contains the above-mentioned grout material of the present invention and water, and is prepared by kneading the grout material and water. The amount of mixing water in the present invention is not particularly limited because it varies depending on the purpose and application of use and the content ratio of each material, but is preferably 10 to 70 parts by mass, more preferably 14 to 65 parts by mass, and even more preferably 16 to 60 parts by mass, relative to 100 parts by mass of grout material. By setting the amount of mixing water to the above lower limit or more, it is possible to suppress a decrease in fluidity and to suppress an extremely large amount of heat generation. In addition, by setting the amount of mixing water to the above upper limit or less, it is possible to ensure strength development.
[0066] In the present invention, the method of mixing the grout material and water is not particularly limited, but it is preferable to use a hand mixer with a rotation speed of 900 rpm or more, a normal high-speed grout mixer, or a twin-shaft forced mixer.
[0067] Mixing with a hand mixer or high-speed grout mixer is preferably performed by, for example, putting a certain amount of water in a container such as a pail or mixer in advance, then adding the grout mortar composition while rotating the mixer, and mixing for 3 minutes or more. Mixing with a forced mixer is preferably performed by, for example, putting the grout mortar composition in advance in the mixer, adding a certain amount of water while rotating the mixer, and mixing for at least 4 minutes. If the mixing time is shorter than the specified time, the grout mortar may not have a proper fluidity due to insufficient mixing.
[0068] [Cured body] The present invention also includes a hardened body made by using the grout mortar composition. More specifically, the mixed grout mortar is usually pumped to the application site by a manual injection gun, a diaphragm hand pump, or a squeeze type mortar pump, and filled. The grout mortar composition of the present invention is applied in this way, and then becomes a hardened body. That is, it becomes a hardened body made by using the grout mortar composition of the present invention. EXAMPLES
[0069] The present invention will be further described below based on experimental examples of the present invention, but the present invention is not limited to these.
[0070] <Evaluation method> (1) Average particle size, average aspect ratio, average circularity The grout admixture prepared in each example was embedded in epoxy resin and then cut with a diamond cutter. It was then polished with #1200 silicon carbide abrasive paper and mirror-finished with an abrasive (3 μm diamond paste). Next, it was etched for 2 seconds using a 33% aqueous solution of ammonium chloride, and then observed under a microscope. The average particle size, average aspect ratio, and average circularity of the di-calcium silicate compound were measured by the method described in the specification. The microscope used was Nikon's "Eclipse E600POL," and the number of samples measured was 4,000. Image analysis software ("IMAGEJ" by Wayne Rasband, National Institutes of Health, USA) was also used.
[0071] (2) Identification of the di-calcium silicate compound The prepared grout admixture was identified by point analysis (50 points) using an EDX (energy dispersive X-ray fluorescence analyzer) and observation under an electron microscope after carbon deposition on the sample surface.
[0072] (3)Chemical composition The measurements were performed using a fluorescent X-ray analyzer, Rigaku's "ZSX-100e."
[0073] (4) Compressive strength remaining ratio The compressive strength at 28 days of age was measured according to JIS R 5201 "Physical Testing Methods for Cement". However, the test specimens were demolded at 1 day of age, sealed and cured until 7 days of age, and then carbonation cured until 28 days of age under conditions of temperature: 20°C, humidity: 60%RH, and CO2 concentration: 5%. After that, to prevent explosion due to moisture loss in the test specimens, they were dried at 105°C for 1 week in a drying furnace, and then heated at 500°C for 3 hours in an electric furnace to obtain test specimens, which were used to measure the compressive strength at room temperature. The compressive strength of the test specimens before drying and heating was also measured at room temperature. The ratio of compressive strength before and after drying and heating was calculated as the compressive strength remaining ratio (compressive strength after drying and heating treatment / compressive strength before drying and heating treatment).
[0074] (5) Neutralization resistance After three hours of heat treatment at 500°C, 4x4x16cm specimens were subjected to accelerated carbonation in an environment of 30°C, 60% relative humidity, and 5% carbon dioxide concentration. After eight weeks, the specimens were cut into slices and a 1% alcohol solution of phenolphthalein was applied to the cut surfaces of the specimens to confirm the carbonation depth. The pretreatment method for the specimens was the same as the test method for the compressive strength residual ratio. That is, the specimens were subjected to carbonation curing up to 28 days as described above, dried at 105°C for one week, and then heated for three hours. Carbonation resistance was evaluated based on the following formula. Carbonation resistance = (carbonation depth after heat treatment + accelerated carbonation (mm) / carbonation depth before heating at 500°C (mm)) x 100
[0075] (6) Liquidity In accordance with JSCE-F 541, the JIS flow value was measured in a 20°C environment immediately after mixing and 30 minutes after mixing.
[0076] (7) Self-healing effect In accordance with JIS A 6206, grout material specimens were prepared in a size of 10cm x 10cm x 40cm under rebar restraint conditions, and after 56 days of age, strain gauges were attached to the surface of the specimens and bending tests were conducted, and the bending test was terminated when cracks of 0.1mm width appeared. After that, the specimens were left to stand for 28 days under conditions of 98% relative humidity and 35°C, and then left to stand for 7 days under conditions of 60% relative humidity and 20°C. After repeating this cycle for 5 times, the ratio of the area where the cracks were closed (closed area / area where cracks appeared) was measured.
[0077] (8) Breeding Bleeding was measured in a 20°C environment in accordance with JIS A 1123.
[0078] Experimental Example 1 A grout material was obtained by preparing 100 parts by mass of cement, 120 parts by mass of fine aggregate, 25 parts by mass of the grout admixture shown in Table 1, and the amounts of expansive agent, hardening agent, gas foaming agent, and water reducing agent shown in Table 2. Note that Experimental Example 2-11 is a grout material that does not contain any grout admixture. 100 parts by mass of the obtained grout material was mixed with 23 parts by mass of water to prepare a grout mortar composition. The prepared grout mortar compositions were measured for fluidity, bleeding, self-healing effect, compressive strength residual ratio, and carbonation resistance. The results are shown in Table 2. Unless otherwise specified, tests were performed at an environmental temperature of 30°C.
[0079] <Materials used> Cement: Ordinary Portland cement, Blaine value 3,450 cm 2 / g Expansion material: Denka CSA#20 - Hardening agent: Calcium aluminate (CaO / Al2O3 molar ratio 2.2, vitrification rate 97%, impurity content 2.0%) Gas foaming material: flaky aluminum powder with stearic acid surface treatment, commercially available Water reducing agent: Naphthalene-based water reducing agent, commercially available product (Daiichi Kogyo Seiyaku Co., Ltd. "Selflo-110P") · Fine aggregate: lime sand, a mixture of 50% 0.6mm and under and 50% 0.6~1.2mm was used. Water: Tap water Grout admixture A: Reagent grade calcium carbonate and reagent grade silicon dioxide were mixed in a molar ratio of 2:1 with 2 parts of reagent grade aluminum oxide, and mixed and ground in a planetary ball mill (FRITSCH). Heat treated at 1,400°C for 2 hours and allowed to cool to room temperature. After that, the mixture was crushed to a size of 3,000 cm2 (the portion passing through a 150 μm sieve) using a Blaine specific surface area of 3,000 cm2. 2 A grout admixture A having a viscosity of 100 / g was prepared. Grout admixture B: Prepared in the same manner as grout admixture A, except that the reagent grade silicon dioxide was replaced with silica sand. Grout admixture C: Prepared in the same manner as grout admixture A, except that the first-grade reagent calcium carbonate was replaced with limestone. Grout Admixture D: Prepared in the same manner as Grout Admixture A, except that the reagent grade silicon dioxide was replaced with fused silica. Grout admixture E: This was prepared in the same manner as grout admixture B, except that silica sand passing through a 150 μm sieve was used. Grout admixture F: Prepared in the same manner as grout admixture A, except that the firing temperature was changed to 1,450°C. Grout admixture G: Prepared in the same manner as grout admixture A, except that the reagent grade silicon dioxide was replaced with silica sand and hand mixing was used instead of mixing and grinding in a planetary ball mill. Grout admixture H: This was prepared in the same manner as grout admixture A, except that the mixing and grinding in a planetary ball mill was replaced by hand mixing. Grout admixture I: This was prepared in the same manner as grout admixture G, except that the residue of silica sand with a sieve size of 150 μm or more was used. Grout Admixture J: Prepared in the same manner as Grout Admixture A, except that the reagent grade silicon dioxide was replaced with fused silica. Grout admixtures A to J were prepared as described above. Each grout admixture was identified by the above method as a DCS compound, and the average particle size, average aspect ratio, average circularity, and chemical composition were measured by the above method, as shown in Table 1.
[0080] [Table 1]
[0081] [Table 2]
[0082] From the results in Table 2, it was confirmed that, as shown in the examples, the inclusion of a grout admixture containing a dicalcium silicate compound with a specific average particle size and average aspect ratio measured by microscopic observation provides high fluidity, inhibits bleeding, and enhances the self-healing effect, and also improves fire resistance and carbonation resistance after exposure to heat. Specifically, a comparison with Experiment No. 2-11, which does not contain a grout admixture, shows that the use of the grout admixture of the present invention significantly improves the compressive strength residual ratio and carbonation resistance. In addition, a comparison with Experiments No. 2-8 and No. 2-9, in which the average particle size deviates from the specific range, shows that the compressive strength residual ratio is improved by including the grout admixture of the present invention, whose average particle size is within the specific range. Moreover, in Test No. 2-10 in which the average aspect ratio was smaller than the specific value, the compressive strength ratio was extremely small and the carbonation resistance was poor.
[0083] Experimental Example 2 The same procedure as in Experimental Example 1 was repeated, except that the mixture was prepared so that it contained 11.1 parts by mass of expansive agent, 0.0025 parts by mass of gas foaming material, 0.5 parts by mass of water reducing agent, 120 parts by mass of fine aggregate, and 25 parts by mass of the grout admixture shown in Table 3, per 100 parts by mass of cement. The results are also shown in Table 4. Grout admixture B-2: Grout admixture B-2 was prepared in the same manner as grout admixture A, except that in the preparation of grout admixture A, the reagent grade silicon dioxide was replaced with silica sand, and the aluminum oxide was replaced with reagent grade aluminum oxide, and the raw materials were mixed so that the chemical composition was as shown in Table 3. Grout admixture B-3: This was prepared in the same manner as grout admixture B-2, except that the raw materials were mixed so that the chemical composition was as shown in Table 3. Grout admixture B-4: This was prepared in the same manner as grout admixture B-2, except that the raw materials were mixed so that the chemical composition was as shown in Table 3. Grout admixture B-5: This was prepared in the same manner as grout admixture B-2, except that in the preparation of grout admixture B-2, first-grade reagent magnesium carbonate (MgCO3) was added as an MgO source, and the raw materials were mixed so that the chemical composition was as shown in Table 3. Grout admixture B-6: This was prepared in the same manner as grout admixture B-5, except that the amount of magnesium carbonate (MgCO3) was changed and the raw materials were mixed so that the chemical composition was as shown in Table 3. Grout admixture B-7: This was prepared in the same manner as grout admixture B-2, except that in the preparation of grout admixture B-2, first-grade reagent gypsum dihydrate (CaSO4·2H2O) was added as an SO3 source, and the raw materials were mixed so that the chemical composition was as shown in Table 3. -Grout admixture B-8: This was prepared in the same manner as grout admixture B-7, except that the amount of gypsum dihydrate (CaSO4·2H2O) was changed. Grout admixture B-9: This was prepared in the same manner as grout admixture B-2, except that in the preparation of grout admixture B-2, first-grade reagent magnesium carbonate (MgCO3) was added as the MgO source, and first-grade reagent gypsum dihydrate (CaSO4·2H2O) was added as the SO3 source, and the raw materials were mixed so that the chemical composition was as shown in Table 3. Grout admixtures B-2 to B-9 were prepared as described above. Each grout admixture was identified by the above method as a DCS compound, and the average particle size, average aspect ratio, average circularity, and chemical composition were measured by the above method as shown in Table 3.
[0084] [Table 3]
[0085] [Table 4]
[0086] Experimental Example 3 The grout admixture B (Blaine specific surface area: 3000 cm 2 The test was carried out in the same manner as in Experimental Example 2, except that a sieve of 1000 g / g was used and passed through a sieve to obtain a grout admixture with a fineness (Blaine specific surface area) shown in Table 5. The results are shown in Table 5.
[0087] [Table 5]
[0088] Experimental Example 4 A test was carried out in the same manner as in Experimental Example 2, except that the grout material was prepared so as to contain the amount of fine aggregate shown in Table 6 relative to 100 parts by mass of cement. The results are shown in Table 6.
[0089] [Table 6] [Industrial Applicability]
[0090] The grout material of the present invention contains a grout admixture containing a di-calcium silicate compound having a specific average particle size and average aspect ratio measured by microscopic observation, and thus provides a grout material, grout mortar composition, and hardened body having high fluidity, suppression of bleeding, and enhanced self-healing effect, as well as improved fire resistance and resistance to carbonation after exposure to heat. Such grout material can be used in a wide range of applications, including civil engineering and construction.
Claims
1. The grout material includes a grout admixture containing a di-calcium silicate compound having an average particle size of 5 to 100 μm as measured by microscopic observation and an average aspect ratio expressed as (major axis diameter / minor axis diameter) of 1.3 or more, cement, an expansive agent and / or a hardening accelerator, a gas foaming substance, a water reducing agent, and a fine aggregate.
2. 2. The grout material according to claim 1, wherein the average circularity of the di-calcium silicate compound, expressed as (4 x pi x area / (perimeter squared)), is 0.8 or less.
3. The chemical composition of the grout admixture is CaO, SiO 2 , Al 2 O 3 , MgO, and SO 3 CaO is 44 to 75 parts by mass, SiO 2 18 to 55 parts by mass of Al 2 O 3 1 to 3 parts by mass, MgO 0 to 5 parts by mass, SO 3 is 0 to 2 parts by mass, and the Blaine specific surface area value of the di-calcium silicate compound is 2,000 to 6,000 cm 2 The grout material of claim 1, wherein the viscosity is 100 / g.
4. The grout material according to claim 1, wherein the content of the fine aggregate is 40 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the cement.
5. A grout mortar composition comprising the grout material according to any one of claims 1 to 4 and water.
6. A hardened body obtained by using the grout mortar composition according to claim 5.
Citation Information
Patent Citations
JP1973078086A
Refractory cement composition
JP2014076917A
Cement-based grout composition
JP3894780B2
Cement composition for grouting and grout material comprising the same
WO2007029399A1
